Active components and molecular mechanism of Syringa oblata Lindl. in the treatment of endometritis based on pharmacology network prediction - Wang, Xiao-Zhen; Song, Xue-Jiao; Liu, Chang; Xing, Chen; Wu, Tong; Zhang, Yue; Su, Jing; Hao, Jing-You; Chen, Xue-Ying; Zhang, Zhi-Yun; Li, Yan-Hua; Liu, Yan-Yan (Frontiers in Veterinary Science, 2022)
Antibiotic treatment of endometritis was limited by the inevitable antibiotic residues and risk of bacterial resistance. Therefore, the development of safe and effective strategies for endometritis treatment is urgently needed. Syringa oblata Lindl (SOL) showed great pharmacological potential against endometritis. However, the active components and underlying mechanism of SOL for endometritis treatment remain indeterminate. In our study, the active components and possible molecular mechanism of SOL against endometritis were predicted through computer data mining and biological networks construction. It was predicted that the main active components of SOL were luteolin, kaempferol, oleanolic acid and rutin, and their anti-endometritis effect was mainly attributed to the TLRs/NF-κB signaling pathway. Furthermore, a green and efficient deep eutectic solvent combined with ultrasound-assisted extraction (UAE-DES) was performed and optimized to obtain high contents of total flavonoid, rutin and luteolin. The four predicted active components in the SOL extracts were qualitatively and quantitatively analyzed by LC/MS and HPLC. Finally, the pharmacological effects of SOL and active components have been verified by a Staphylococcus aureus-endometritis models in mice. H&E staining, bacterial load in uterus tissues assays initially validated the pharmacodynamic effects of SOL and quantitative real-time PCR (RT-qPCR) and ELISA results confirmed that SOL and four active components could ameliorate the uterus injury caused by Staphylococcus aureus, the mechanism of action is related to the TLRs/NF-κB signaling pathway.